Caracteristicas físicas, mecánicas e hidráulicas evaluadas en el pavimento flexible del corredor vial San Juan – El Arenal - Calvopiña Ponce, Dennys Adrian (2025)
In the present research, an evaluation of various properties of the flexible pavement along the San Juan – El Arenal road corridor, located in the province of Chimborazo, Ecuador, is presented. This evaluation considers the pavement's primary functions safety and comfort and examines its constitutive parameters in order to understand the behavior of the material and the relationships among its characteristics. The motivation behind this study lies in identifying the needs and interrelations of the physical, mechanical, and hydraulic conditions of the existing pavement. A comprehensive methodology was applied, both in the field and in the laboratory, to analyze physical properties such as grain size distribution, Atterberg limits, and densities, which are essential factors for ensuring the pavement's strength and durability throughout its service life. Likewise, mechanical and hydraulic characteristics were assessed, focusing on parameters that define the pavement's resistance and the runoff coefficient of the asphalt layer. One of the key aspects of this research is the application of core extraction techniques, which serve as a fundamental method for obtaining representative samples from the asphalt layer, thereby enabling an in-depth assessment of its current condition. The results obtained are expected not only to provide a detailed understanding of the current state of this roadway but also to set a precedent for future studies and contribute to the updating of technical standards.